Use of Social Media Celebrity Influencers in Promoting Hospitality Business Brand in Nigeria: A Public Relations Perspective - Emmanuel Olumuji; Semiu Bello (LSPR Institute of Communication & Business, 2025)
This study takes a theoretical approach to examine the interconnectedness of brand management, influencer marketing, and public relations within Nigeria’s hospitality industry, focusing on the growing role of social media celebrity influencers. Brands serve as symbolic constructs that shape consumer perceptions, emotional connections, and purchasing decisions. Successful branding extends beyond differentiation to foster trust, loyalty, and engagement. With the rise of digital media, public relations strategies have evolved, allowing hospitality businesses to leverage influencers for enhanced visibility and consumer connection. These influencers, perceived as credible and aspirational figures, play a pivotal role in shaping consumer attitudes and brand perception. To maximise the impact of influencer marketing, Nigerian hospitality business owners are to carefully select influencers whose values align with their brand identity. Reliable partnerships foster stronger consumer trust and engagement. Stakeholders need to integrate conventional and modern branding elements, focusing on consistent visual identity, consumer experiences, and reputation management. Emotional connections, built on shared values and positive brand experiences, are essential for long-term success. Additionally, PR experts should utilise data analytics to guide strategic decision-making in brand management, influencer partnerships, and service delivery. By adopting a holistic, data-driven approach to influencer marketing and public relations, hospitality businesses can enhance their competitive edge, sustain growth, and navigate the evolving dynamics of Nigeria’s digital marketplace.